História de vida e características de personalidade de agressores conjugais : um olhar psicanalítico - Stenzel, Gabriela Quadros de Lima (2015)
Domestic violence against women is considered a serious public health problem in Brazil and worldwide. Studies with marital aggressors seem to be fundamental to the understanding of such violence so common nowadays. The main goal of this thesis was to investigate life history and personality characteristics of men who perpetrated violence against women, held in the Central Prison of Porto Alegre. It consists of three sections: one theoretical and two empirical. The first section is theoretical, and aimed to search subsidies to understand how traumatic events in this men childhood may influence on the relations they will establish with others and their capacity to control the free expression of aggressiveness (death drive) in adult s romantic relationships. The concept of narcissism, as an organizer or deconstructive process of the psyche, was used to understand the psychological functioning of the marital aggressor. The second section, empirical (developed from qualitative methodological assumptions), introduced the study that aimed to cover the research project main objective, which was conducted with the participation of three men (marital aggressors). All men answered to a Personal and Socio-Demographic Data Sheet, MINI Interview, the Rorschach Method and a series of three semi-structured interviews guided by three main topics, respectively: a) the participant's life story; b) marital choices and the presence of violence in romantic relationships and c) the current situation in prison as a result of violence committed. The results were examined through Interpretative Analysis and grounded on assumptions of psychoanalytic theory. Three assertions have been identified: a) helplessness and violence as marks in the life history and psychic constitution of marital aggressors; b) marital choice and the perpetuation of violence as manifestations of narcissistic failure and c) Maria da Penha Law and the recover experience of the feeling of abandonment. It was possible to understand the violence committed as a result of a life story marked by traumatic experiences that produced narcissistic failure and the free expression of aggressiveness (death drive). The third and final section, also of empirical nature, explored the interconnections between trauma, narcissism and death drive through a clinical case analysis of one of the research participants. The influence of life history in the marital relationship and in the violent act committed by this man was explored, as well as his personality characteristics. The presence of helplessness and violence in his life story were identified, producing marks on his psychic constitution that influenced in his romantic relationship. It is proposed the term psychic imprisonment as a means of understanding the violence perpetrated.